Composite lead-acid storage battery structure and manufacturing process
By adding sheet-like magnetic materials on both sides of the lead-acid battery plate to form a stable magnetic field, the problem of inconsistent conversion of surfactant substances on the traditional lead-acid battery plate is solved, extending the battery's service life and improving the structural strength and stability of the battery.
Patent Information
- Application Number
- CN202510101346.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-22
AI Technical Summary
Due to the unevenness of the plate manufacturing process and the discreteness of the electrochemical reactions in traditional lead-acid batteries, the conversion of active substances is inconsistent, resulting in local sulfateization, sludgeization of live substances, corrosion and other problems on the surface of the plate, thereby reducing the stability and service life of the battery.
Add sheet-like magnetic materials to both sides of the pole plate of the lead-acid battery to form a stable magnetic field to guide the crystallization uniformity of reaction substances such as lead, lead sulfate, and lead oxide during the mutual conversion process, and at the same time improve the structural strength of the battery.
By guiding the uniform crystallization of the reaction substance, the recycling life of the battery is extended, the structural strength and stability of the battery are improved, the charging and discharging efficiency is enhanced, and the battery capacity retention rate is improved.
Smart Images

Figure CN119864516A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lead-acid battery preparation technology, in particular to a composite lead-acid battery structure and a manufacturing process. Background Art
[0002] Lead-acid batteries are batteries composed of a shell, positive and negative plates, separators, sulfuric acid electrolyte and terminal columns. As an electrochemical energy storage device, its reaction chemical equation is as follows:
[0003] Discharge process:
[0004] Negative electrode reaction: Pb-2e - +SO4 2- =PbSO4
[0005] Positive electrode reaction: PbO2+2e - +4H++SO4 2- =PbSO4+2H2O
[0006] Overall reaction: Pb + PbO2 + 2H2SO4 = 2PbSO4 + 2H2O
[0007] Charging process:
[0008] Negative electrode reaction: PbSO4+2e - =Pb+SO4 2-
[0009] Positive electrode reaction: PbSO4+2H2O=PbO2+2e - +4H++SO4 2-
[0010] Overall reaction: 2PbSO4+2H2O=Pb+PbO2+2H2SO4
[0011] The charging and discharging process of the battery is completed through the mutual conversion of active substances on the positive and negative electrode surfaces. However, due to the discreteness of the electrochemical reaction and the heterogeneity of the plate manufacturing process, there will be differences in the conversion of active substances, which will gradually accumulate, causing local sulfation, muddling, corrosion and other defects on the plate surface, ultimately leading to battery failure. This is also one of the important factors for the short cycle life of traditional lead-acid batteries.
[0012] In addition, most lead-acid batteries are 12V batteries, which are composed of 6 cells inside. Each cell is composed of a positive and negative plate group, and the clusters are welded in series through the tabs to form a whole. Due to the structural design of the 6 cells arranged in series, the cells on both sides of the battery have differences in parameters such as pressure and heat dissipation from the 4 cells in the middle, which further reduces the consistency and stability of the battery, resulting in a decrease in the stability and service life of the battery.
[0013] Chinese patent CN107170966B discloses a magnetic paste process for power type lead-acid batteries, including: a) material preparation: preparing positive lead paste raw materials according to the following components and weight percentages:
[0014] Lead powder 68-75wt%, red lead 5-7wt%, 4BS 1-3wt%, conductive polymer 0.8-2.4wt%, carbon material 0.05-0.4wt%, short fiber 0.05-0.18wt%, water 10-13wt%, sulfuric acid solution 7-9wt%; prepare the negative electrode lead paste raw material according to the following components and weight percentages:
[0015] Lead powder 78-82wt%, surfactant 0.1-0.8wt%, composite carbon material 0.15-0.8wt%, inorganic salt 0.5-1.2wt%, short fiber 0.05-0.18wt%, water 9-12wt%, sulfuric acid solution 7.5-8.7wt%;
[0016] b) Premixing: Add the conductive polymer and carbon material in the positive electrode lead paste raw material into water, and after complete infiltration, ultrasonically treat for 0.3 to 1 hour at a water bath temperature of 55 to 63°C, then stir at a speed of 500 to 700 rpm for 0.5 to 1.5 hours, stir evenly, add short fibers and shear for 1 to 2 minutes to prepare a positive electrode mixed solution for standby use;
[0017] The composite carbon material, inorganic salt and surfactant in the negative electrode lead paste raw material are added to water at 72-80°C, and after being completely soaked, ultrasonic treatment is performed for 0.5-0.8 hours, and then stirred at a speed of 400-600 rpm for 0.3-1.2 hours. After stirring evenly, short fibers are added thereto and sheared for 1-2 minutes to prepare a negative electrode mixed solution for standby use;
[0018] c) Wet mixing: within 1 to 2 minutes after the positive electrode mixed solution and the negative electrode mixed solution are prepared, the lead oxide lead powder in the positive electrode lead paste raw material and the lead oxide lead powder in the negative electrode lead paste raw material are added thereto at a uniform speed, and wet mixing and stirring are performed for 3 to 5 minutes to prepare the positive electrode wet mixed material and the negative electrode wet mixed material respectively;
[0019] d) Acid mixing: Slowly add the sulfuric acid solution in the positive electrode lead paste raw material and the sulfuric acid solution in the negative electrode lead paste raw material to the positive electrode wet mixture and the negative electrode wet mixture obtained in the above steps respectively for acid mixing and stirring, and finally obtain the positive electrode lead paste and the negative electrode lead paste respectively; the magnetic field is applied during the step c) wet mixing and the step d) acid mixing. This scheme increases the magnetic field effect during the wet mixing and acid mixing processes, affects the electrochemical reaction process in the lead-acid battery and paste process, accelerates the charge transfer rate, improves the conversion efficiency of active substances, and makes the generated lead sulfate particles finer and more uniform. This method requires the manufacturers of positive and negative electrode materials of lead-acid batteries to improve their production equipment. For the intermediate manufacturers of lead-acid batteries, since the purchased positive and negative electrode materials have been produced, they cannot be assembled to obtain lead-acid batteries with better performance. Summary of the invention
[0020] The purpose of the present invention is to overcome the problem of short cycle life of existing lead-acid batteries and provide a composite lead-acid battery structure and manufacturing process. By adding rigid sheet magnetic materials on both sides of the battery parallel to the pole plates, the consistency of the conversion reaction of the active material of the battery pole plates and the consistency between the monomers are improved, thereby extending the service life of the battery.
[0021] The specific plan is as follows:
[0022] A composite lead-acid battery comprises a bottom slot, in which at least one pole piece group is installed, the pole piece group comprises a plurality of pole plates, a middle cover adapted to the bottom slot is arranged on the top of the pole piece group, the middle cover is provided with a terminal for being electrically connected to the pole piece group, and a cover sheet adapted to the middle cover is provided on the top of the middle cover; storage slots are provided on both sides of the bottom slot parallel to the direction of the pole plates, and sheet-shaped magnetic materials are inserted into the storage slots.
[0023] Furthermore, the sheet magnetic material is a single piece or a combination of multiple pieces, the magnetic field direction is the same when the multiple pieces are placed in combination, and the material is an alloy soft magnetic material composed of Fe, Co, Ni, Mn, Mg, Zn, Cu, C or rare earth metal elements, or a hard magnetic material.
[0024] Furthermore, the sheet-like magnetic material has a thickness of 0.3 to 10 mm and an area of 2 to 150 cm 2 .
[0025] Furthermore, the sheet magnetic material is a ferrite or cast alloy hard magnetic material with a thickness of 0.8 to 4.0 mm; or the sheet magnetic material is a low-carbon steel or iron-based alloy soft magnetic material with a thickness of 2.0 to 8 mm. The above scheme can ensure that the strength of the magnetic field is within a suitable range, and at the same time, the strength of the battery is improved to reduce the failure rate of bulging deformation.
[0026] Furthermore, compared with a lead-acid battery with the same structure and a composite non-magnetic material, the composite lead-acid battery has a lower assembly pressure, a lower internal resistance of the battery in a fully charged state, an improved coulombic efficiency, an improved battery cycle life, and an improved battery capacity retention rate.
[0027] The present invention also protects a preparation process of the composite lead-acid battery, comprising the following steps:
[0028] S1, combining lead-acid battery monomers to form a semi-finished battery;
[0029] S2, using hard magnetic material or soft magnetic material through solenoid coil or permanent magnet contact magnetization to obtain sheet magnetic material;
[0030] S3, placing the sheet magnetic material into the storage slots on both sides of the semi-finished battery through a slotting machine with the magnetic field direction being the same and parallel to the pole piece direction;
[0031] S4, after the battery is capped, filled with liquid and formed, a composite lead-acid battery is manufactured.
[0032] Furthermore, the lead-acid battery cells described in S1 are arranged in a continuous structure or a 2*3 structure.
[0033] Furthermore, the sheet-shaped magnetic material in S2 is a Fe-Ni-Mo alloy material, and the size of a single sheet of magnetic material is 145*68*3 mm.
[0034] Furthermore, the sheet-shaped magnetic material described in S2 is a carbon-containing steel alloy material, and the size of a single sheet of magnetic material is 75*47.5*4mm.
[0035] Beneficial effects: (1) The composite lead-acid battery uses sheet magnetic materials to form a stable magnetic field inside the lead-acid battery, which can guide the crystallization uniformity of lead, lead sulfate, lead oxide and other reaction substances during the conversion process during the battery cycle, thereby extending the cycle life of the battery;
[0036] (2) The sheet-like magnetic materials on both sides have a certain rigidity, which can improve the structural strength of the lead-acid battery and reduce the failure rate of bulging and deformation;
[0037] (3) The thickness of the sheet magnetic material can be adjusted during the preparation process, which can increase the battery assembly pressure, reduce the battery internal resistance, and improve the charging and discharging efficiency.
[0038] (4) Adding sheet magnetic materials on both sides can reduce the differences in parameters such as pressure and heat dissipation between the outermost cells and the middle cells of the battery, thereby improving the consistency and stability of the battery operation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings will be briefly introduced below. Obviously, the accompanying drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0040] Figure 1 This is a schematic diagram of the structure of a composite lead-acid battery provided by Embodiment 1 of the present invention;
[0041] Figure 2 This is a schematic diagram of the storage tank structure provided by Embodiment 1 of the present invention;
[0042] Figure 3 This is a schematic diagram of the structure of a composite lead-acid battery provided by Embodiment 2 of the present invention;
[0043] Figure 4 It is a schematic diagram of the storage tank structure provided by an embodiment 2 of the present invention;
[0044] Figure 5 This is a cycle life test data diagram provided by Example 3 of the present invention;
[0045] Figure 6 This is a cycle life test data diagram provided by Example 4 of the present invention. DETAILED DESCRIPTION
[0046] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.
[0047] The charge and discharge test in the following embodiments refers to the life reliability test of GB / T22199.1-2017 recommended standard 5.11. After the battery is fully charged, it is discharged at a current of 1.0I2 (A) for 1.8 hours in an environment of 25℃±2℃, and then charged at a constant voltage (U) of 60±0.50V (current limit 0.4I2 A) for 10.2 hours; the above is a life reliability number. The test is terminated when the battery terminal voltage is lower than 42V±0.10V after three consecutive discharges of 1.8 hours, and these three cycles are not counted in the life reliability number.
[0048] Example 1
[0049] A composite lead-acid battery structure, such as Figure 1 and Figure 2As shown, it includes a bottom slot 1, a pole piece group 2 is installed in the bottom slot 1, the pole piece group 2 includes a plurality of pole plates, and a middle cover 4 adapted to the bottom slot 1 is located on the top of the pole piece group 2, thereby realizing the encapsulation of the pole piece group 2. The middle cover 4 is provided with a terminal 5 for electrical connection with the pole piece group 2, including a positive terminal and a negative terminal, and a cover sheet 6 adapted to the middle cover 4 is provided on the top of the middle cover 4.
[0050] The bottom groove 1 is provided with receiving grooves 7 on both sides parallel to the pole plate direction, and the sheet-like magnetic material 3 is inserted into the receiving grooves 7. The sheet-like magnetic material 3 forms a stable magnetic field inside the lead-acid battery, which can guide the crystallization uniformity of the reaction substances such as lead, lead sulfate, and lead oxide in the process of mutual conversion during the battery cycle, thereby extending the cycle life of the battery.
[0051] In the above structure, adding sheet magnetic materials on both sides of the battery parallel to the plate direction can form a stable magnetic field inside the lead-acid battery, which can guide the crystallization uniformity of lead, lead sulfate, lead oxide and other reaction substances in the process of mutual conversion during the battery cycle, thereby extending the cycle life of the battery. At the same time, the sheet magnetic material has a certain rigidity, which can improve the structural strength of the lead-acid battery, reduce the failure rate of bulging deformation, increase the battery assembly pressure, and improve the consistency and stability of the battery.
[0052] Example 2
[0053] A composite lead-acid battery structure, such as Figure 3 and Figure 4 As shown, this embodiment increases the capacity of the lead-acid battery on the basis of the embodiment 1, 3 lead-acid batteries in the embodiment 1 are assembled, and the bottom tank 1 is enlarged by 2 times on the basis of the embodiment 1 to accommodate 3 parallel arranged pole piece groups 2. Each pole piece group 2 is provided with receiving grooves 7 on both sides parallel to the pole plate direction, and there are 6 receiving grooves 7 in total.
[0054] Example 3
[0055] The composite lead-acid battery in Example 1 is prepared by the following main steps:
[0056] S1, combining lead-acid battery cells, using a structure in which 6 cells are arranged continuously, to form a semi-finished battery;
[0057] S2, using Fe-Ni-Mo alloy material as the magnetic material, the size of a single piece of magnetic material is 145*68*3mm, and there are 2 pieces on both sides to obtain a sheet magnetic material;
[0058] S3, placing the sheet magnetic material into the storage slots on both sides of the semi-finished battery through a slotting machine with the magnetic field direction being the same and parallel to the pole piece direction;
[0059] S4, after the battery is capped, filled with liquid and formed, a composite lead-acid battery is manufactured.
[0060] The rated voltage of the battery is 12V, the designed capacity of the battery is 20Ah, the assembly pressure is 42kPa, the internal resistance of the fully charged state is 9.8mΩ, and the tested charging and discharging coulomb efficiency is 98%.
[0061] Compared with a lead-acid battery with the same structure but without magnetic materials (i.e., the lead-acid battery without the storage groove 7 and the sheet magnetic material 3 based on Example 1), the assembly pressure is 36 kPa, the internal resistance in the fully charged state is 11.5 mΩ, and the charging and discharging coulomb efficiency is tested to be 95%.
[0062] like Figure 5 As shown, according to the T / ZJXDC 001-2021 standard 7.10 life reliability test, the cycle life of the composite lead-acid battery in this embodiment is increased by 41%.
[0063] Example 4
[0064] The composite lead-acid battery in Example 2 is prepared by the following main steps:
[0065] S1. Combine lead-acid battery cells into a 2*3 arrangement of 6 cells to form a semi-finished battery;
[0066] S2. Use low carbon steel alloy material as magnetic material, the size of a single piece of magnetic material is 75*47.5*4mm, and there are 6 pieces on both sides to obtain sheet magnetic material;
[0067] S3, placing the sheet magnetic material into the storage slots on both sides of the semi-finished battery through a slotting machine with the magnetic field direction being the same and parallel to the pole piece direction;
[0068] S4, after the battery is capped, filled with liquid and formed, a composite lead-acid battery is manufactured.
[0069] The rated voltage of the battery is 12V, the designed capacity of the battery is 12Ah, the assembly pressure is 95kPa, the internal resistance of the fully charged state is 12.2mΩ, and the tested charging and discharging coulomb efficiency is 98%.
[0070] Compared with a lead-acid battery with the same structure and composited with non-magnetic materials (i.e., excluding the storage groove 7 and the sheet-like magnetic material 3 based on Example 2), the assembly pressure is 85 kPa, the internal resistance in the fully charged state is 13.5 mΩ, and the charging and discharging coulomb efficiency is tested to be 96%.
[0071] like Figure 6As shown, according to the T / ZJXDC 001-2021 standard 7.10 life reliability test, when the number of cycles is the same, the capacity retention rate of the composite lead-acid battery in this embodiment is increased by 13% by comparing the same type of structural battery (i.e., rated voltage 12V, battery capacity 12Ah, no magnetic material) at the same number of cycles.
[0072] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0073] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0074] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A composite lead-acid battery, comprising a bottom tank, characterized in that: At least one pole piece group is installed in the bottom groove, and the pole piece group includes multiple pole plates. A middle cover adapted to the bottom groove is arranged on the top of the pole piece group, and the middle cover is provided with terminals for electrical connection with the pole piece group. A cover sheet adapted to the middle cover is provided on the top of the middle cover; storage grooves are provided on both sides of the bottom groove parallel to the direction of the pole plates, and sheet magnetic materials are inserted into the storage grooves.
2. The composite lead-acid battery according to claim 1, characterized in that: The sheet magnetic material is a single piece or a combination of multiple pieces. When the multiple pieces are placed together, the magnetic field direction is the same. The material is an alloy soft magnetic material composed of Fe, Co, Ni, Mn, Mg, Zn, Cu, C or rare earth metal elements, or a hard magnetic material.
3. The composite lead-acid battery according to claim 2, characterized in that: The sheet-like magnetic material has a thickness of 0.3 to 10 mm and an area of 2 to 150 cm 2 .
4. The composite lead-acid battery according to claim 3, characterized in that: The sheet-shaped magnetic material is a ferrite or cast alloy hard magnetic material with a thickness of 0.8 to 4.0 mm; or the sheet-shaped magnetic material is a low-carbon steel or iron-based alloy soft magnetic material with a thickness of 2.0 to 8 mm.
5. The composite lead-acid battery according to any one of claims 1 to 4, characterized in that: Compared with a lead-acid battery with the same structure and made of non-magnetic materials, the composite lead-acid battery has reduced assembly pressure, reduced internal resistance of the battery in a fully charged state, improved coulomb efficiency, improved battery cycle life, and improved battery capacity retention rate.
6. A process for preparing the composite lead-acid battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, combining lead-acid battery monomers to form a semi-finished battery; S2, using hard magnetic material or soft magnetic material through solenoid coil or permanent magnet contact magnetization to obtain sheet magnetic material; S3, placing the sheet magnetic material into the storage slots on both sides of the semi-finished battery through a slotting machine with the magnetic field direction being the same and parallel to the pole piece direction; S4, after the battery is capped, filled with liquid and formed, a composite lead-acid battery is manufactured.
7. The preparation process of the composite lead-acid battery according to claim 6, characterized in that: The lead-acid battery cells described in S1 are arranged in a continuous structure or a 2*3 structure.
8. The preparation process of the composite lead-acid battery according to claim 6, characterized in that: The sheet-shaped magnetic material described in S2 is a Fe-Ni-Mo alloy material, and the size of a single sheet of magnetic material is 145*68*3mm.
9. The preparation process of the composite lead-acid battery according to claim 6, characterized in that: The sheet-shaped magnetic material described in S2 is a carbon steel alloy material, and the size of a single sheet of magnetic material is 75*47.5*4mm.
Citation Information
Patent Citations
A magnetic and paste process for power-type lead-acid batteries
CN107170966B
Cited By
Lead-acid storage battery
CN120357050A